2020
DOI: 10.1016/j.quascirev.2020.106169
|View full text |Cite
|
Sign up to set email alerts
|

Holocene dynamics of the southern westerly winds over the Indian Ocean inferred from a peat dust deposition record

Abstract: The southern westerly winds (SWW) play a major role in climate variability in Southern Hemisphere mid-and high-latitudes, regulating rainfall, ocean circulation, and the Southern Ocean carbon sink. Despite their importance, little is known about millennial scale changes in the SWW and how they have influenced the climate system in the past and interacted with the Earth's surface elements, such as dust, nutrients and carbon. Here we present a dust record from a 6.6 kyr old peat core in Amsterdam Island (AMS) si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 101 publications
1
10
0
Order By: Relevance
“…Gili et al (2019), indicated the Sr, Nd and Pb isotope ratios of Antarctic modern dust recovered from snow samples collected along coastal sites of the Dronning-Maud Land area (DML-East Antarctica), which showed similar composition to the Southern Africa sediments. This data is consistent with the results observed by Vanderstraeten et al (2019) Ultimately, another study carried out in a core from the Southern Indian Ocean, has also proposed a mixing model where SSA and SAF have been found to be the main distal dust sources through most of the Holocene (Li et al, 2020). In resume, we have presented different evidences indicating the transport of SAF material reaches the South Atlantic sector of the Southern Ocean and the marginal sites of East Antarctica.…”
Section: Atmospheric Circulation Pattern and Dust Deposition Over Antarcticasupporting
confidence: 92%
“…Gili et al (2019), indicated the Sr, Nd and Pb isotope ratios of Antarctic modern dust recovered from snow samples collected along coastal sites of the Dronning-Maud Land area (DML-East Antarctica), which showed similar composition to the Southern Africa sediments. This data is consistent with the results observed by Vanderstraeten et al (2019) Ultimately, another study carried out in a core from the Southern Indian Ocean, has also proposed a mixing model where SSA and SAF have been found to be the main distal dust sources through most of the Holocene (Li et al, 2020). In resume, we have presented different evidences indicating the transport of SAF material reaches the South Atlantic sector of the Southern Ocean and the marginal sites of East Antarctica.…”
Section: Atmospheric Circulation Pattern and Dust Deposition Over Antarcticasupporting
confidence: 92%
“…Chronology. Age model output of the AMS peat core is adopted from ref 39 . In brief, a total of 20 samples were picked for plant macrofossils and subsequently radiocarbon-dated at the LMC14 Artemis Laboratory (Saclay, France, SacA code) or GADAM center (Gliwice, Poland, GdA code).…”
Section: Methodsmentioning
confidence: 99%
“…Chronology. Age model output of the AMS peat core is adopted from 38 . In brief, a total of 20 samples were picked for plant macrofossils and subsequently radiocarbon-dated at the LMC14 Artemis Laboratory (Saclay, France, SacA code) or GADAM center (Gliwice, Poland, GdA code).…”
Section: Methodsmentioning
confidence: 99%